Problems of environmental audit in the aviation branch of Ukraine - Білявський, Г.О.; Марченко, Д.В. (Proceedings of National Aviation University (archive), 2009)
This article discusses the problems of eсological audit in the aiviation sphere of Ukraine. Shows major reasons, factors, objects, subjects and ways of their solution. Mentioned recommendations and role of ecological audit and ecological pasportization for sustainable development of this industry and Ukraine as a whole. Proposed basic requirements forsystem guarante of ecological-audit activity in our country according to international standards and european regulations.